Efficient N-formylation of primary aromatic amines using novel solid acid magnetic nanocatalyst. Issue 67 (12th November 2020) - Yadav, Jitendra Kumar; Yadav, Priyanka; Awasthi, Satish K.; Agarwal, Alka
Abstract : Sulfonic acid functionalized over biguanidine fabricated silica-coated heterogeneous magnetic nanoparticles (NP@SO3 H) have been synthesized, well characterized and explored for the first time, as an efficient and recyclable catalyst for N -formylation of primary amines under mild reaction conditions. Abstract : Sulfonic acid functionalized over biguanidine fabricated silica-coated heterogeneous magnetic nanoparticles (NP@SO3 H) have been synthesized, well characterized and explored for the first time, as an efficient and recyclable catalyst for N -formylation of primary amines under mild reaction conditions. Exploiting the magnetic nature of Fe3 O4, the prepared catalyst was readily recovered from the reaction mixture via an external magnet. The catalyst can be reused for up to six cycles without any substantial loss of catalytic activity. The cost effectiveness, simple methodology, wide substrate tolerance, excellent yield and easy work-up are the additional advantages of present catalytic system.